Sibling Role, Parenting Pattern, Maternal Education and Knowledge, and Their Associations with Speech-Language Ability of Children Aged 3-5 Years Old in Karanganyar, Central Java - Siswanto, Arif; Murti, Bhisma; Adriani, Rita Benya (Journal of Maternal and Child Health, 2017)
Background: Speech-language ability is one of several developmental abilities that must be masters by children under-five. Data from the Central Biro of Statistics showed that in 2014 there were 131 children under-five with speech-language ability problem. This study aims to determine the associations between sibling role, parenting pattern, maternal education and knowledge, and speech-language ability of children 3-5 years old. Subjects and Method: This was an analytic observational study using cross sectional design. The study was carried out in Gondangrejo Sub-District, Karanganyar District, Central Java. A sample of 80 children aged 3-5 years old were selected for this study by random sampling. The dependent variable was speech